1976
DOI: 10.1083/jcb.69.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Action of dichlorobenzimidazole riboside on RNA synthesis in L-929 and HeLa cells.

Abstract: A BSTR ACT 5,6-Dichloro-l-/~-o-ribofuranosylbenzimidazole (DRB) inhibits RNA synthesis in L-929 cells (mouse fibroblast line) and HeLa cells (human epithelioid carcinoma line) within 2 min of addition of the compound to the medium. By removing DRB from the medium, the inhibition is promptly and completely reversed after treatment of cells for as long as I h or even longer. The inhibitory effect of DRB on the overall rate of RNA synthesis is similar in L and HeLa ceils and is markedly concentration-dependent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 33 publications
8
69
0
Order By: Relevance
“…Thus, polyoma virus RNA synthesis was almost completely inhibited by DRB, while cellular RNA synthesis was only partially inhibited. These results are consistent with previous findings (Granick, 1975;Tamm et al, 1976;Tamm, 1977;Fraser et al, 1978) that DRB preferentially inhibits RNA synthesis directed by RNA polymerase II, which is responsible for transcription of polyoma virus DNA (Shmookler et al, 1974). Fig.…”
Section: Effect Of Drb On Cellular and Virus Rna Synthesissupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, polyoma virus RNA synthesis was almost completely inhibited by DRB, while cellular RNA synthesis was only partially inhibited. These results are consistent with previous findings (Granick, 1975;Tamm et al, 1976;Tamm, 1977;Fraser et al, 1978) that DRB preferentially inhibits RNA synthesis directed by RNA polymerase II, which is responsible for transcription of polyoma virus DNA (Shmookler et al, 1974). Fig.…”
Section: Effect Of Drb On Cellular and Virus Rna Synthesissupporting
confidence: 83%
“…DRB inhibits uptake of [3H]uridine into mammalian cells (Sehgal et al, 1976;Tamm et al, 1976). Measurement of the effect of DRB on RNA synthesis by incorporation of exogenous [3H]uridine must therefore be corrected for this inhibition.…”
Section: Effect Of Drb On Cellular and Virus Rna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…DRB was originally discovered as an inhibitor of the synthesis of heterogeneous nuclear RNA in human, murine, avian, and insect cells (Egyhazi 1974;Granick 1975;Sehgal et al 1976a;Tamm et al 1976). Many of these studies showed that DRB inhibits the synthesis of full-length RNA transcripts by enhancing the pausing or premature termination of transcription by RNA Pol II.…”
mentioning
confidence: 99%
“…The action of DRB is selective for RNA polymerase II transcripts; RNA polymerase III 5S and tRNA-specific transcripts and the rates of RNA polymerase I-mediated rRNA synthesis are all not affected (1). Initial reports (2,3) indicated that DRB acted at or very close to the site of initiation of transcription, on the basis of incorporation of [3H]uridine into specific-size mRNAs of Balbiani rings in Chironomus (2) and of the labeling kinetics of HeLa cell mRNA precursors (3). The effect of adding DRB to HeLa cells is very rapid (<5 min).…”
mentioning
confidence: 99%